Problem wartościowania dziedzictwa kulturowego a jego funkcjonalne uwarunkowania w ujęciu kulturoznawczym - Bełkot, Andrzej (Studia Etnologiczne i Antropologiczne, 2012)
The cultural studies analyses basing on a socio‑regulating conception of culture understand culture and cultural heritage in a very similar way. The difference could consist in perceiving culture more „procedurally” and cultural heritage more „subjectively”. The former would refer to the thought reality, the latter to its content. However, in both cases, they take on the form of cultural regulations that is why the division suggested is fairly arbitrary in nature. The main subject of considerations is the problem of complex relations between the means of a conscious development of the cultural heritage and its dependence of objective conditions. In the light of theory‑cultural assumptions, worldview valorizations influence the ultimate form of cultural heritage less significantly than the demand of social practice. Despite it, the components of socio‑subjective regulators are mental in character, and depend directly on their previous historical forms. Thus, one cannot totally abandon or overcome cultural heritage. Even though particular regulating beliefs or their whole units deactualize in culture, they can exist in social awareness after the meaningful recontextualization under the label of precious „cultural traces” or relics deprived of symbolic values.